Social Media Fatigue Management among Adolescents: Rapid Review - Kurniawan Kurniawan; Yuni Nur’aeni; Shafira Aulia Mujahidah; Puput Nugraha; Siti Zahra; Afnani Aquino (Fakultas Kedokteran, 2023)
Background: Fatigue is when the body feels tired, lethargic, and has no energy. Fatigue is a medical condition that can range from mild to severe. One form of fatigue is social media fatigue. This fatigue is experienced mainly by teenagers as active social media users. Purpose: This rapid review aims to determine which social media management can be implemented by teenagers to overcome fatigue. Methods: This study was a rapid review, in which the search for journal articles uses the PubMed, CINAHL, Google Scholar, Cochrane Library, and The Lancet databases with full-text inclusion criteria from 2012-2022 and in Indonesian and English and selected using PRISMA. Result: found five journal articles explaining several interventions, namely Fatigue In Teenagers on the Internet (FITNET), Cognitive Behavioral Therapy (CBT), Cognitive-Behavioral Group Therapy (CBGT), and family or parent counseling therapy. Conclusion: Social media fatigue can be managed to control internet use for internet addicts and teenagers with fatigue.